International Currencies and Endogenous Enforcement : An Empirical Analysis - Prem, Roohi (IMF Working Papers; Working Paper ;, 1997)
This paper investigates the determinants of the international role of a currency. It argues that standard determinants such as monetary performance and financial openness are at best imperfect indicators of a currency's stability prospects, because the issuer's promise of stability is not exogenously enforceable. The paper advocates an enforcement approach to international currencies that make explicit the underlying incentive incompatibilities. Additional enforcement determinants of currency internationalization are identified. The model is estimated using time-series cross-sectional analysis for three data sets. Monetary performance-related standard determinants fail to exhibit explanatory power, whereas the enforcement determinants are strongly significant and robust.